Understanding additive manufacturing : rapid prototyping, rapid tooling, rapid manufacturing - Gebhardt, Andreas (Hanser Publishers, 2012)
Additive Manufacturing (AM) is the worldwide used term for layer oriented or generative manufacturing which originally was introduced at the end of the 1980s as Rapid Prototyping. Within the last 20 years it has developed dramatically. Today it is not just a valuable tool for making models and prototypes, but a manufacturing method for final parts as well as for mold inserts. It spreads throughout all disciplines and branches of industry, from art to medicine and from car manufacturing to aerospace engineering. AM is about to revolutionize the manufacturing technology in general. This book is designed as a supporting material not only for special courses on advanced manufacturing technology, but for up-dating the content of traditional manufacturing lessons. It also provides basic information to facilitate self studies and is a valuable quick guide to AM.